2021
DOI: 10.31557/apjcp.2021.22.10.3055
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Tobacco Control Policy at District Level in Indonesia: A Qualitative Analysis

Abstract: Introduction: Comprehensive tobacco control policies are lacking in Indonesia where smoking prevalence in males is among the highest in the world. This study aims to explore the knowledge, attitude, opportunities and challenges to tobacco control among local stakeholders. Methods: This is a qualitative study using in-depth interviews. Four study areas included Bengkulu Province, Bengkulu City, Seluma District, and Kaur District. Eighteen participants interviewed were fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…These findings align with previous studies establishing the impact of family and friend smoking behavior on cigarette smoking among young people (Huang et al, 2014;Joung et al, 2016;Wellman et al, 2016). The results also show how young Indonesians are surrounded by outdoor tobacco adverts near home, near schools, on social media, and by family and friends who smoke Wulan et al, 2022;Nasution et al, 2022;Dewi et al, 2022;Yunarman et al, 2021). This would lead to more adult smokers as studies have shown that youth smoking predicts adult smoking (Paavola et al 1996).…”
Section: Resultsmentioning
confidence: 73%
“…These findings align with previous studies establishing the impact of family and friend smoking behavior on cigarette smoking among young people (Huang et al, 2014;Joung et al, 2016;Wellman et al, 2016). The results also show how young Indonesians are surrounded by outdoor tobacco adverts near home, near schools, on social media, and by family and friends who smoke Wulan et al, 2022;Nasution et al, 2022;Dewi et al, 2022;Yunarman et al, 2021). This would lead to more adult smokers as studies have shown that youth smoking predicts adult smoking (Paavola et al 1996).…”
Section: Resultsmentioning
confidence: 73%
“…In Indonesia, three primary factors determining current tobacco use are pocket money, tobacco-branded products used by the community, and easy access to cigarettes near schools (Lucia et al, 2022;Nurhayati et al, 2022). The challenges in implementing tobacco control policies in Indonesia are mainly due to political structure, policy hierarchy, complex bureaucracy, unclear roles and responsibilities, and high levels of corruption (Astuti et al, 2020;Yunarman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Berbeda dengan penelitian tersebut, Azkha (2013) menyebutkan bahwa sumber daya manusia dalam implementasi KTR di Kota/Kabupaten studi di Sumatera Barat dirasa cukup dengan dibentuknya tim pengawasan, pemantau, dan penegak perda serta adanya keterlibatan lintas sektor dalam pelaksanannya. b. Sumber Daya Keuangan Empat dari artikel yang ditinjau menyebutkan adanya keterbatasan anggaran dalam implementasi KTR di wilayah studinya (Nasution et al, 2022;Rizal et al, 2021;Siregar et al, 2022;Yunarman et al, 2021). Keterbatasan anggaran mengurangi kemampuan untuk menegakkan kepatuhan dan penyediaan sarana dan prasarana yang mendukung (Yunarman et al, 2021).…”
Section: Metode Hasilunclassified
“…b. Sumber Daya Keuangan Empat dari artikel yang ditinjau menyebutkan adanya keterbatasan anggaran dalam implementasi KTR di wilayah studinya (Nasution et al, 2022;Rizal et al, 2021;Siregar et al, 2022;Yunarman et al, 2021). Keterbatasan anggaran mengurangi kemampuan untuk menegakkan kepatuhan dan penyediaan sarana dan prasarana yang mendukung (Yunarman et al, 2021). Sementara itu, beberapa artikel menyebutkan sumber pembiayaan dalam implementasi KTR di wilayah studinya berasal dari APBD (Ariska, 2017;Azkha, 2013;Rizal et al, 2021) dan pemanfaatan Dana Bagi Hasil Cukai Hasil Tembakau (DBHCHT) (Azkha, 2013).…”
Section: Metode Hasilunclassified
See 1 more Smart Citation